Isolation of mouse CD44 cDNA: structural features are distinct from the primate cDNA. - Nottenburg, C (1989)
CD44 is a glycoprotein that participates in adhesion of lymphocytes to high endothelial cells of lymph organs and likely functions in other intercellular adhesions as well. We have isolated a mouse CD44 cDNA by polymerase chain reaction amplification of cDNA synthesized from total cellular RNA isolated from 38C-13, a B-lymphocyte cell line. The oligonucleotide sequences were based at the 5' end on the baboon CD44 sequence upstream of and including the translation initiator ATG and at the 3' end on a mouse CD44 sequence that was determined from a rare, incomplete cDNA clone. The mouse CD44 DNA sequence is similar to the baboon CD44 sequence but has structural features that are distinct. The external domain has a region that is only 35% similar between the mouse and primate proteins, in contrast to 85%-90% similarity in the rest of the sequence. In addition, just upstream from the predicted cleavage site of the leader peptide, nucleotide insertions result in the addition of two or four amino acids, depending upon the mouse strain. An amino acid replacement between two strains carrying different CD44 (also called Pgp-1) allotypes is likely responsible for the Pgp-1 polymorphism. The most striking aspect of mouse CD44 is that the RNA does not fractionate with polyadenylylated RNA, unlike the CD44 RNA in human, baboon, rat, and chicken.